Higher‐quality diet and non‐consumption of meat are associated with less self‐determined disability progression in people with multiple sclerosis: A longitudinal cohort study. (26th August 2021) - Simpson‐Yap, Steve; Nag, Nupur; Probst, Yasmine; Jelinek, George; Neate, Sandra
Abstract: Background and purpose: Modifiable lifestyle factors, including diet, may affect clinical outcomes in multiple sclerosis (MS). This study assessed the relationships between diet, and disability, fatigue, and depression risk in people with MS. Methods: Participants from the Health Outcomes and Lifestyle In a Sample of people with Multiple sclerosis (HOLISM) international cohort were assessed over 2.5 years. Dietary data were obtained using a modified Diet Habits Questionnaire (DHQ), disability using the calculated Patient‐determined MS Severity Score (P‐MSSS), fatigue using the Fatigue Severity Scale, and depression risk using the Patient Health Questionnaire‐2. Participants reported whether they were experiencing symptoms due to a recent relapse. Cross‐sectional and prospective relationships of diet and disease outcomes were explored, adjusted for relevant confounders. Results: Among 1, 346 participants, higher DHQ scores showed significant dose‐dependent associations with lower frequencies of severe disability, fatigue, and depression risk, cross‐sectionally. Prospectively, higher baseline DHQ scores were associated with a lower risk of increasing disability, those above the median having 41% and 36% lower risk of increasing disability, and 0.30 P‐MSSS points less disability progression, but were not associated with fatigue or depression risk. Meat consumption was associated with 0.22 P‐MSSS points higher disability cross‐sectionally, while prospectively, baseline meat consumption was associated with 76% higher risk of increasing disability and 0.18 P‐MSSS points higher disability progression. Dairy consumption showed mixed associations cross‐sectionally and prospectively. Conclusions: These results show that better quality of diet, as well as not consuming meat, were associated with reduced disability progression in people with MS. Substantiation of these findings in other settings may inform opportunities to manage disability progression in people with MS using dietary modifications. Abstract : In this cohort of 1, 346 people with multiple sclerosis, followed over 2.5 years, we found that better diet quality and not consuming meat or dairy were associated with significantly less disability progression. Those with better diet quality or not consuming meat or dairy actually decreased their disability, while those with worse diet practices had static or worse disability. However, no prospective associations of diet quality with fatigue or depression were seen.